Brass Diva : The Life and Legends of Ethel Merman - Flinn, Caryl (Book collections on Project MUSE., 2007)
Broadway star Ethel Merman's voice was a mesmerizing force and her vitality was legendary, yet the popular perception of La Merm as the irrepressible wonder falls far short of all that she was and all that she meant to Americans. This biography tells the story of how the stenographer from Queens, New York, became the queen of the Broadway musical.